Dynamic high energy density plasma environments at the National Ignition Facility for nuclear science research. (9th February 2018) - Cerjan, Ch J; Bernstein, L; Hopkins, L Berzak; Bionta, R M; Bleuel, D L; Caggiano, J A; Cassata, W S; Brune, C R; Fittinghoff, D; Frenje, J; Gatu-Johnson, M; Gharibyan, N; et al.
Abstract: The generation of dynamic high energy density plasmas in the pico- to nano-second time domain at high-energy laser facilities affords unprecedented nuclear science research possibilities. At the National Ignition Facility (NIF), the primary goal of inertial confinement fusion research has led to the synergistic development of a unique high brightness neutron source, sophisticated nuclear diagnostic instrumentation, and versatile experimental platforms. These novel experimental capabilities provide a new path to investigate nuclear processes and structural effects in the time, mass and energy density domains relevant to astrophysical phenomena in a unique terrestrial environment. Some immediate applications include neutron capture cross-section evaluation, fission fragment production, and ion energy loss measurement in electron-degenerate plasmas. More generally, the NIF conditions provide a singular environment to investigate the interplay of atomic and nuclear processes such as plasma screening effects upon thermonuclear reactivity. Achieving enhanced understanding of many of these effects will also significantly advance fusion energy research and challenge existing theoretical models.